Public Services in the Field of Basic Health for Mothers and Children in Talawaan District, North Minahasa Regency, North Sulawesi Province - Sambiran, Sarah; Kolondam, Helly F.; Punuindoong, Aneke Y. (Journal of Management and Administration Provision, 2024)
Maternal mortality rate and infant mortality rate are an indication of the low level of population welfare. Likewise, the high disparity in socio-economic levels - rich and poor, between regions and between urban and rural areas. Therefore, health services for mothers and children are the main priority in health development. The government at all levels of government has established and implemented health programs for mothers and children. However, it has not provided a good impact on the aspect of basic public services. Health services for mothers and children through integrated service posts are more visible at the village level and require serious attention from the government because they are very far from health service centers such as regional hospitals. Therefore, this study was conducted to describe and explain basic public health services for mothers and children in Talawaan District, North Minahasa Regency. This study is considered important from the aspect of public health and related to strengthening social capital in the superior fields of social humanities, arts and culture as well as the development and strengthening of institutional systems, health policies, and community empowerment in the superior fields of health and medicine in the Sam Ratulangi University research strategy plan. Data were collected through interviews with the Head of the Health Service and Health Center, Posyandu officers and pregnant mothers and those with toddlers. Observations were made by looking directly at basic health services in Talawaan District. Secondary data were collected during health service activities and conducting electronic searches on Google Scholar and ResearchGate. The analysis was carried out based on the stages of reduction, interpretation, drawing conclusions and verification/triangulation. The research findings that public services in the field of basic health are accessible, acceptable, fair and safe for mothers and children but are not yet fully efficient and effective in their implementation. The concept found from this study is that the community needs basic health services for mothers and children that are easy to access and accept, fair to all levels of society and medically safe. While the principles of efficiency and effectiveness are more about the interests of the organization in the use of resources and achieving goals.